Peningkatan Hasil Belajar Siswa Melalui Model Problem Based Instruction Pada Mata Pelajaran Seni Budaya Kelas X AKL 1 SMKN 2 Palu - Nasriani Mohammad Syahril (Universitas Tadulako, 2022)
The aim of this study was to improve the learning outcomes of class X AKL students at SMKN 2 Palu through the application of the Problem Based Instruction model in the Cultural Arts subject. This research method is classroom action research. The instrument used in this study was a learning outcome test. The data analysis method used is descriptive for qualitative data and quantitative data. The results obtained from this study are changes in student learning outcomes of class X AKL 1 after the application of the Problem Based Instruction model. In the first cycle the average score of students was 75.60 with classical completeness 66.67%, then in the second cycle the average score of students increased to 87.80 with classical completeness 96.67%. From cycle I to cycle II there was an increase in the average grade and classical completeness of class X AKL 1 SMKN 2 Palu. The conclusion of this study is that the Problem Based Instruction learning model can improve student learning outcomes in class X AKL 1 SMKN 2 Palu in the subject of Cultural Arts.